Target site pharmacokinetics of doxycycline for rosacea in healthy volunteers is independent of the food effect. (17th August 2018) - Pal, Arindam; Matzneller, Peter; Gautam, Anirudh; Österreicher, Zoe; Wulkersdorfer, Beatrix; Reiter, Birgit; Stimpfl, Thomas; Zeitlinger, Markus
Abstract : Aims: Doxycycline (DFD‐09) oral capsules 40 mg are approved for the treatment of inflammatory lesions of rosacea. Unlike the food‐induced lowering of doxycycline's peak plasma concentration (Cmax ), its exposure under fed conditions in the skin, the drug's target site for rosacea, is unknown. The present study explored the effect of food on the dermal pharmacokinetics of doxycycline. Methods: The pharmacokinetics of doxycycline in the dermal interstitial fluid (d‐ISF) and plasma of healthy volunteers were assessed in parallel groups under fed ( n = 6) and fasting ( n = 6) conditions during a 14‐day once‐daily treatment course with doxycycline oral capsules 40 mg (DFD‐09). Sampling of d‐ISF and plasma was performed on days 1, 10 (fasting group d‐ISF only) and 14. Results: Twelve subjects were randomized, and 11 analysed. No causally drug‐related adverse events occurred. Dermal doxycycline exposures (Cmax and area under the curve) under the fed state were about 30% lower than under the fasting state at day 1 but were similar at steady state. In analogy to skin, plasma exposure showed no between‐group difference at steady state. Accumulation ratios were higher in the skin than in plasma. Correcting for plasma protein binding (~90%), dermal doxycycline exposure was approximately threefold higher than unbound plasma exposure. Conclusions: At steady state, doxycycline concentrations in the skin of fed and fasting healthy volunteers were comparable. Doxycycline's efficacy in rosacea is possibly due to considerable dermal accumulation of unbound doxycycline and is independent of the effect of food.